PENGEMBANGAN MODEL PENGELOLAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PAI DI SEKOLAH DASAR SE- KECAMATAN LUBUK SIKARAH KOTA SOLOK - Rifdahayati Rifdahayati (IAIN Batusangkar, 2016)
This research due to the learning Islamic Education (PAI) at grade IV Primary School Lubuk Sikarah Solok was focused on cognitive aspects, the learning management less managed by the teacher so that the learning management tends to be static. This research was aimed at producing a model of learning management for PAI at grade IV Primary School Lubuk Sikarah Solok. This research was classified into Research and Development by using Thiagarajan model (define, design, develop and dissemination). Data were collected through validation techniques, observation and interviews. The findings showed that the model was valid with 80.625%; and practical with 79.025%. Keywords: Model, Management, Learning, Islamic Education